PENGARUH PROMOSI, IMAGE JURUSAN, HARGA, DAN LOKASI TERHADAP KEPUASAN SISWA - Suyamto . (KELOLA, 2013)
The purpose of this research was to prove the influence of promotion, Image of program study, price and location to students’ satisfaction at The State Vocational High School 4 Klaten individually and simultaneously. The Hypothesis in this research were : there was significant influence among promotion, Image of program study, price and location to students’ satisfaction at The State of Vocational High School 4 Klaten individually and simultaneously as well. The method used in this research was a survey using questionaries for getting data. Population was students at The State of Vocational High School 4 Klaten. Sample taken with a quota random sampling. The test had done with a multiple regression, t test, F test and R 2 . Regression model test showed that promotion, Image of program study price and location had significance influence toward students’ satisfaction individually. The Result F test showed that promotion, Image of program study, price and location had significance influence toward students satisfaction simultaneously and R test had 0,940 so the independent variables could explain dependent variables was more 94,0%. The result of test which had been conducted with the regression model , t test, F test and also R test had proved that The fourth of the variables above could become the predictor to the variable of students’ satisfaction. Keyword : promotion, Image of program study, price, location, satisfaction.